Impact of the European Society of Gastrointestinal Endoscopy 2020 guidelines on the number of scheduled post-polypectomy surveillance colonoscopies - Bustamante-Balén, Marco; García-Campos, Maria; Lorenzo-Zúñiga, Vicente; Alonso-Lázaro, Noelia; Sanchez-Montes, Cristina; Argüello-Viudez, Lidia; Pons-Beltrán, Vicente (Endoscopy International Open, 2022)
Background and study aims In contrast with the European Society of Gastrointestinal Endoscopy (ESGE) 2013 and the US Multi-society Task Force (USMSTF) 2020 guidelines, the ESGE 2020 guideline considers patients with three to four adenomas < 10 mm or an adenoma with villous histology as low risk. The aim of this study was to quantify the influence of the application of the new ESGE 2020 guidelines, as opposed to the ESGE 2013 and USMSTF 2020 guidelines, on the number of scheduled colonoscopies, and to describe the main causes for changes in the surveillance intervals.Patients and methods A retrospective evaluation was conducted of a prospectively maintained fecal immunochemical test (FIT)-based regional colorectal cancer screening program database. Surveillance regimens following ESGE 2020, ESGE 2013, and USMSTF 2020 guidelines were compared.Results Overall, 1284 individuals with a positive FIT and undergoing colonoscopy were consecutively included. When applying the ESGE 2020 guidelines, 10.8 % of patients changed to a “no-surveillance” group (relative reduction in colonoscopies of 82.5 %). The main reason for these changes was considering three to four adenomas as low risk. The proportion of patients from the “3-year surveillance” group who moved to the “no-surveillance” group was lower when a sessile serrated lesion (SSL) was present (ESGE 2013, 32.0% vs 16.3 %; USMSTF 2020 17.2 % vs 6.8 %). Analyzing the 41 patients with SSLs who remained unchanged in the “no-surveillance” group, only in 15 (36.6 %) the cause was the presence of an SSL.Conclusions applying the new ESGE 2020 guidelines could reduce by 11 % the proportion of individuals being offered surveillance. SLLs have not a major influence on the change of surveillance intervals.